Tadlis Al-Kammiyyah dalam Praktik Takaran BBM pada Pom Mini: Analisis Hukum Ekonomi Syariah - Ramadan; Relit Nur Edi; Susi Nur Kholidah (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The rapid growth of motor vehicles has driven the proliferation of small-scale fuel retail businesses commonly known as pom mini or pertamini. This phenomenon conceals a serious problem, namely dishonest fuel measurement practices that systematically harm consumers. This study aims to examine fuel measurement practices at pom mini outlets from the perspective of Islamic economic law, analyze the relevance of fiqh muamalah principles to transaction validity, and identify legal protection mechanisms for consumers. A descriptive qualitative approach grounded in field research was employed, utilizing observation, in-depth interviews, and documentation as data collection techniques, analyzed through the Miles and Huberman model reinforced by source and method triangulation. Findings reveal three predominant measurement deviation patterns: machine calibration manipulation, use of unrecertified measuring instruments, and unilateral termination of fuel dispensing. All identified patterns are categorized as tadlis al-kammiyyah, rendering the sale contract legally fasid under Islamic jurisprudence. Consumer protection is available through two complementary dimensions, namely Sharia norms via the concept of khiyar and the principle of amanah, alongside positive law through the Consumer Protection Act and legal metrology regulations. A synergistic approach combining internalization of muamalah values, periodic regulatory oversight, and consumer legal literacy constitutes the most comprehensive and sustainable solution recommended by this study